2006
DOI: 10.1097/01.bpb.0000191867.93022.88
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic outcome of soft-tissue surgery for hip subluxation in non-ambulatory children with cerebral palsy

Abstract: This study reviewed radiographs of non-ambulatory spastic tetraparetic cerebral palsy patients who underwent soft tissue hip surgery to address hip subluxation. Patients were under 10 years of age at surgery, had limited hip motion, and radiographic subluxation. At an average 7.4 years postoperatively, hips had a migration percentage in the normal range (0-15%) in 58 of 70 cases (83%). Hips with preoperative subluxation between 30 and 49% had a normal migration percentage in 18 of 21 cases (81%), and those ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“… 13 ) reported that patients with lack of preoperative coverage > 50% were at risk for femoral head coverage deterioration despite adductor release. Bowen and Kehl 14 ) also reported that hips with a preoperative MP of 30–49% had a normal MP (< 15%) in 18 of 21 cases (81%) postoperatively, whereas those with a preoperative MP > 50% had a normal MP in three of seven (43%) cases postoperatively. They reported that soft-tissue release surgery alone, even in cases of moderate hip subluxation, could result in long-term radiographic hip stability.…”
Section: Discussionmentioning
confidence: 93%
“… 13 ) reported that patients with lack of preoperative coverage > 50% were at risk for femoral head coverage deterioration despite adductor release. Bowen and Kehl 14 ) also reported that hips with a preoperative MP of 30–49% had a normal MP (< 15%) in 18 of 21 cases (81%) postoperatively, whereas those with a preoperative MP > 50% had a normal MP in three of seven (43%) cases postoperatively. They reported that soft-tissue release surgery alone, even in cases of moderate hip subluxation, could result in long-term radiographic hip stability.…”
Section: Discussionmentioning
confidence: 93%
“…For 63 (68%) patients with initial subluxated hips (MP > 25%) it was good, and for 30 patients with "hips at risk" (MP 25%) it was 100% good shows the value of the initial MP as a predictive factor. Bowen and Kehl [12] consider it necessary to identify precisely which hips will subluxate without treatment (studies show 26-78%), however, without more complete knowledge of the natural history of each hip, or the impossibility of close monitoring, most surgeons will intervene in smaller MPs, as in our study patients.…”
Section: Discussionmentioning
confidence: 95%
“…Adductor tenotomies, and surgeries involving the psoas and hamstrings (16%), or those that associate hamstrings had better results compared to adductor surgery alone or with psoas, with statistical significance. Kalen and Bleck [1], found better results including the psoas than with isolated adductor tenotomies, and other authors include the psoas release frequently [6,12].…”
Section: Discussionmentioning
confidence: 97%
“…The cutoff value of MP ≥50% is consistent with several studies that consider an MP <50% a good outcome after surgery. 15 , 16 , 24 , 25 Since the 1980s, some authors 26 28 have suggested that if soft tissue surgery is executed before MP has reached 50%, further luxation may be prevented. Conversely, preoperative MP >50% has been associated with poor outcome after soft tissue surgery.…”
Section: Discussionmentioning
confidence: 99%